2011
DOI: 10.21061/jcte.v26i1.492
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development Needs of Idaho Technology Teachers: Teaching and Learning

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This data are then analyzed and the items are ranked with those having the highest MWDS considered the most pressing professional development needs. Previous research has been critiqued for solely focusing on the perceptions of teachers, leading to the possibility that true professional development needs are not being identified (Cannon, Kitchel, Duncan, & Arnett, 2011). By considering the perceptions of school leaders such as district superintendents, as well as teachers, a better understanding of what the true needs are may be developed.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…This data are then analyzed and the items are ranked with those having the highest MWDS considered the most pressing professional development needs. Previous research has been critiqued for solely focusing on the perceptions of teachers, leading to the possibility that true professional development needs are not being identified (Cannon, Kitchel, Duncan, & Arnett, 2011). By considering the perceptions of school leaders such as district superintendents, as well as teachers, a better understanding of what the true needs are may be developed.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The work by agricultural education researchers over the last sixteen years has provided a foundation for needs assessment in other CTE program areas; such as engineering and technology, business and marketing, family and consumer sciences, and skilled and technical sciences (trades and industrial) (Cannon et al, 2011;Kitchel, Cannon, & Duncan, 2009. CTE teachers as a group, excluding agricultural educators, have identified "teaching students to think critically and creatively", "motivating students to learn", "designing and developing digital-age learning experiences and assessments", and "utilizing website development and software" as teaching and learning priorities (Cannon et al, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…An Idaho Technology Teacher needs assessment showed that mathematics placement test scores were significantly affected by more math‐enhanced agricultural power and technology curriculum. The teachers of these courses requested professional development activities based on how to teach students critical thinking and problem‐solving (Cannon, Kitchel, Duncan, & Arnett, ). However, this would be an academic need, not a STEM need.…”
Section: Review Of Literaturementioning
confidence: 99%